1981
DOI: 10.1128/jb.145.1.321-327.1981
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone biosynthesis in Bacillus subtilis: isolation of men mutants and evidence for clustering of men genes

Abstract: Menaquinone (vitamin K2)-deficient mutants of Bacillus subtilis were selected by ultaneous resistance to two aminoglycoside antibiotics. These men mutants fell into two groups: group I, in which the nutritional requirement was satisfied either by o-succinylbenzoic acid or by 1,4-dihydroxy-2-naphthoic acid; and group II, comprising those capable of growing only when supplemented with 1,4-dihydroxy-2-naphthoic acid. The latter group could be further subdivided into two classes on the basis of syntrophy experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
(26 reference statements)
4
17
0
Order By: Relevance
“…typhimurium men mutants, when tested by streaking side by side on glycerol fumarate or glycerol TMAO plates (7), did not cross-feed each other. Similarly negative results were obtained in the studies of men mutants in E. coli (4, 5), although such cross-feeding studies were successful in Bacillus subtilis (12). However, we found that cross-feeding with respect to providing intermediates for H2S production was easily detected.…”
supporting
confidence: 83%
“…typhimurium men mutants, when tested by streaking side by side on glycerol fumarate or glycerol TMAO plates (7), did not cross-feed each other. Similarly negative results were obtained in the studies of men mutants in E. coli (4, 5), although such cross-feeding studies were successful in Bacillus subtilis (12). However, we found that cross-feeding with respect to providing intermediates for H2S production was easily detected.…”
supporting
confidence: 83%
“…It has previously been shown that Gram-positive bacilli are capable of utilizing exogenous DHNA to satisfy nutritional requirements in organisms with mutations in genes upstream of MenA (Meganathan et al, 1981;Taber et al, 1981); thus, the observation that addition of DHNA to the culture medium does not rescue bacterial growth in the presence of Ro 48-8071 indicated that the inhibition likely occurs at a step in menaquinone biosynthesis downstream of the action of MenB, a hypothesis supported by the observation that Ro 48-8071 specifically inhibits MenA activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…men Mutants of Bacillus subtlis Mutants of B. subtilis, an organism that does not contain ubiquinone, were obtained by nitrosoguanidine treatment and were selected by simultaneous resistance to two aminoglycoside antibiotics by Taber and his colleagues (209). The use of aminoglycoside antibiotic resistance for the selection of men mutants derives from the role of quinones in transport of these antibiotics into the bacterial cell (36,210).…”
Section: Genetics Of Menaquinone Biosynthesis Men Mutants Of Eschericmentioning
confidence: 99%